Civic engagement and giving behaviors: The role of empathy and beliefs about poverty. Issue 3 (3rd May 2016) - Luengo Kanacri, Bernadette Paula; González, Roberto; Valdenegro, Daniel; Jiménez-Moya, Gloria; Saavedra, Patricio; Mora, Eduardo Andrés; Miranda, Daniel; Didier, Lucas Silva; Pastorelli, Concetta
ABSTRACT: The current study explores different routes to civic involvement by identifying how a context-specific dimension of empathy and beliefs of autonomy and dependency might jointly predict different types of giving behaviors (i.e., monetary donations), which in turn should predict civic engagement. The sample consisted of 1, 294 participants (656 females) between the ages of 18 to 64 ( M age = 38.44, SD = 14.71), randomly selected from seven different cities in Chile. Even after controlling for gender, age, and the socioeconomic status of participants, results mainly support the role of giving behaviors as drivers of actual engagement in civic life. Monetary donations, in turn, are predicted by higher levels of empathy toward poverty and autonomy-oriented beliefs. Implications of these findings are discussed in terms of agentic perspectives on civic participation.